An Empirical Examination Of The Relationship Between Firm's Fundamental Variables And Systematic Risk: Empirical Evidence From Malaysian Stock Market - Zatalifard, Farhad (2009)
This study investigates the relationship between the fundamentals variables and systematic risk in Bursa Malaysia formally known as KLSE. The financial and market information were collected from data stream database and other recognised website such as KLSE.com.my and reuters.com for the period January 2003 to December 2007. The relationship between seven fundamental variables including asset turnover, equity turnover, liquidity ratio, payout ratio, and firm size, debt to equity ratio, and opening profit margin and systematic risk was tested by using a multiple regression analysis.